Touchstone [ Level 1 - McCarthy; McCarten; Sandiford; Aldcorn (Cambridge, UK ; New York: Cambridge University Press, 2005)
System requirements for accompanying CD-ROMs: IBM-PC or compatible; Windows 98 or higher
To accompany textbook titled "Touchstone : Level 1 / Michael McCarthy, Jeanne McCarten, Helen Sandiford"
"New series that offers a fresh approach to teaching and learning North American English"--P. [4] cover
Keywords: English language -- -- Textbooks for foreign speakers